2021
DOI: 10.3390/jcm11010170
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Consequences of the COVID-19 Pandemic on Members of the General Population in Italy: A Preliminary Study on Executive Inhibition

Abstract: The pandemic period which has characterized the last two years has been associated with increasingly worsening psychological conditions, and previous studies have reported severe levels of anxiety, mood disorder, and psychopathological alteration in the general population. In particular, worldwide populations have appeared to present post-traumatic stress symptoms (PTSS). Surprisingly, no studies have evaluated the effect of COVID-related PTSS on cognitive functioning. This study focused on the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Thus, it was expected that it would immediately impact the population as a whole with severe psychological and cognitive implications. Indeed, our findings are in line with previous literature on COVID-19 which report the presence of cognitive decline in the short [ 20 , 42 , 53 ], medium [ 49 , 52 , 61 ], and long-term periods [ 50 , 92 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, it was expected that it would immediately impact the population as a whole with severe psychological and cognitive implications. Indeed, our findings are in line with previous literature on COVID-19 which report the presence of cognitive decline in the short [ 20 , 42 , 53 ], medium [ 49 , 52 , 61 ], and long-term periods [ 50 , 92 ].…”
Section: Discussionsupporting
confidence: 93%
“…Only two studies were performed on healthy people by using standardized tests. The study by Pisano et al [ 20 ], performed in the first four months of the lockdown measures (short period), reported a worsening in working and prospective memory performance in a group of 150 college students; while in the medium period, the only study by Favieri et al [ 52 ] showed impaired executive functioning and motor inhibition in a sample of 90 college students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age of the participants was 22.5±2.5 years (18)(19)(20)(21)(22)(23)(24)(25). The average Body Mass Index (BMI) is 21.5±5.5.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the impact of COVID-19 on mild cognitive disorder (MCD) has rarely been studied, unlike that of other respiratory diseases [ 11, 12 ]. Cognitive impairment may be related to both biological processes [ 13–15 ] and social conditions, specific limiting quarantine conditions or stressful life circumstances that may occur under lockdown conditions [ 16 ]. Many studies were conducted in hospitals, specialized COVID wards and research institutions, while research rarely focused on the primary care perspective [ 17 ].…”
Section: Introductionmentioning
confidence: 99%